The competitive advantage of a peripheral university town: Human and social capital perspectives from Joensuu, Finland - Teemu Makkonen (European Regional Science Association (ERSA), 2012)
The positive impacts of social and human capital on individual, firm and geographical level are well known. Accordingly, the literature on social capital has advocated the impacts of social networks, norms and trust in securing individual and mutual benefits. Already, the early literature on human capital was concentrated on the economic advantage of individuals, that is, on the impact of education on wage levels. Recent economic studies underline the importance of human capital in creating firm-level innovations and fostering regional economic development. The role of universities has been highlighted in this discussion. However, it seems that this educated human capital is geographically concentrated on the largest urban regions. Whether, this imposes difficulties for firms located in more peripheral regions is discussed here with a case study from a small university town of Joensuu situated in peripheral Eastern Finland. The proposition presented here is that the negative impacts of locational factors, in the periphery, and having a small labour pool will be partially compensated with close social ties and worker immobility. First, the question is approached through official statistics showing that the mobility of educated workforce is smaller in more rural and peripheral regions compared to that of the capital and other densely-populated regions of Finland. Second, the tentative picture drawn from the statistics is deepened with data from semi-structured thematic interviews conducted in Joensuu. The main stakeholders interviewed were chosen, according to the framework of regional innovation systems, from both public and private organizations (n = 15). The results confirm that although a peripheral location of firms does impose limitations to the availability of human capital at hand, the negative impact is compensated with low outmigration of educated workers due to existing well-knit social ties. Furthermore, employee loyalty to their employers is high in Joensuu, that is, the thinner possibilities for other employment renders the educated workforce in Joensuu relatively immobile even in intraregional scale. Although, worker immobility can be seen as a drawback for a region it can also be considered as a regional asset for firms that have decided to locate their activities in Joensuu, as it saves the firms from the mandatory allocation of resources to the training and introductory procedures of new employees. Accordingly, a local university both attracts and supplies educated workers in the region for the benefit of local enterprises and is an important partner in cooperation for local firms.
Keywords: 330